Answer:
The solution for x is [tex]x = 0[/tex]
Step-by-step explanation:
The first step to solve this equation is placing everything with the exponential to one side of the equality, and everything without the exponential to the other side. So
[tex]e^{x} = 1[/tex]
The first part is already how we want, so ok.
Now, we need to know that the ln and the exponential are inverse functions. This means that, for example, [tex]\ln{e^{x}} = x[/tex].
So, applying ln to both sides
[tex]\ln{e^{x}} = \ln{1}[/tex]
[tex]x = 0[/tex]